Investigation into the contribution of neutral hydrogen mass in galaxy cluster by using small radio telescope / Mohd Shaiful Rizal Hassan - Mohd Shaiful Rizal, Hassan (2017)
A single pointing observation by using small radio telescope is considerably important in tracing the amount of neutral hydrogen (HI) in cluster of galaxies as a whole. This spectral line analysis, centered at 21-cm provides an insight of the HI behaviour in clusters of galaxies. Cluster A262 has been chosen as the best candidate for the study because of its properties that fit with the instrument‟s capability and source‟s visibility at the location of the telescope. In addition, the chosen of A262 is based on the characteristics such as (a) it is a spiral rich cluster and (b) it is distributed unevenly throughout the edge of the cluster, which represents a good approximation of HI mass (MHI) location. Several spectra have been identified that show significant detection from A262, which peaked near to source velocity, 4890 km/s. The study has shown that 21-cm spectral line observation by using small radio telescope yields the source velocity, v = 4970 km/s (slightly different from literature) which contribute to HI mass of about MHI = (6.22 ± 0.32) × 1011 Mʘ. The estimated MHI is then being compared with virialized mass of the cluster, MVT. MVT indicates the total mass of the cluster which is obtained from spectroscopic analysis – MVT = (7.16 ± 0.09) × 1013 Mʘ. Spectroscopic analysis also provides the information of how HI mass being distributed in the cluster – by determining the location of HI rich galaxies resides in the cluster. Finally, the contribution of dark matter mass, MDM in A262 has been deduced, which is believe to be the major building block for most of clusters of galaxies (~ 97%). All the results presented in this study were compatible with previous studies and meet the objectives of the study. Thus, the technique used in this study is then quantified as reliable, rather than using a raster scanning, which is more suitable for observation on individual galaxy.